Harvard business review on managing uncertainty (Harvard Business School P. BostonUS, 1999)
Identifies levels of uncertainty which a company can face and provides a framework which can assist executives in thinking through uncertainty and its implications for strategy. Examines the role of planning in corporate learning. Suggests strategies for decision making, and shows how companies which change proactively can achieve success.\n \n
Located in the Learning Resource Centre